2017
DOI: 10.5853/jos.2016.01802
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Approach to Decrease In-Hospital Delay for Stroke Thrombolysis

Abstract: Background and Purpose Decreasing the time delay for thrombolysis, including intravenous thrombolysis (IVT) with tissue plasminogen activator and intra-arterial thrombectomy (IAT), is critical for decreasing the morbidity and mortality of patients experiencing acute stroke. We aimed to decrease the in-hospital delay for both IVT and IAT through a multidisciplinary approach that is feasible 24 h/day. Methods We implemented the Stroke Alert Team (SAT) on May 2, 2016, which introduced hospital-initiated ambulance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Earlier treatment would also reduce the risk of symptomatic intracranial hemorrhage. [26,27] In Korea, there have been continuing efforts on reducing the time delay for patients with stroke using the stroke code system based on the computerized physician order entry system [9,27]. Actually, our data showed that mean time from door to initiation of treatment was continuously decreasing (up to 41.1 min for IV t-PA or 113 min for groin puncture).…”
Section: Discussionmentioning
confidence: 81%
“…Earlier treatment would also reduce the risk of symptomatic intracranial hemorrhage. [26,27] In Korea, there have been continuing efforts on reducing the time delay for patients with stroke using the stroke code system based on the computerized physician order entry system [9,27]. Actually, our data showed that mean time from door to initiation of treatment was continuously decreasing (up to 41.1 min for IV t-PA or 113 min for groin puncture).…”
Section: Discussionmentioning
confidence: 81%
“…The hospitals in the present study did not use a protocol for hospital prenotification by emergency medical services. Additionally, the behavior and actions of the ED staff with patients with minor stroke may differ in hospitals with such prenotification systems [4,21,22]. Therefore, possible differences in the hospitals' care systems should be considered when interpreting our results.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical studies also have shown that the shortening of treatment time for tPA was not often accompanied by improvements in clinical outcomes [3,4,20]. However, previous meta-analyses with larger sample sizes have demonstrated the benefit of rapid treatment even in patients with minor stroke [1,21]. Although no obvious difference in functional outcomes was found in this study, we think that every effort should be made to reduce the time delay even in patients with minor stroke, as is recommended in guidelines [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that complications are associated with worse outcome in those patients 23 . Further, in Korea, the nurses are included in the Stroke Alerts Teams (SAT) organized with the aim to accelerate time to thrombolysis in the patients with AIS 24 . In London, where 8 hyper-acute stroke units were established in 2010, the nursing staff is involved in thrombolysis treatment in terms of the patients' fulfillment of criteria for receiving this therapy, providing accommodation and adequate care 25 .…”
Section: Discussionmentioning
confidence: 99%